Functional characterization of mutants in the transmembrane domains of the rat P2X7 receptor that regulate pore conductivity and agonist sensitivity - Jindrichova, Marie; Bhattacharya, Anirban; Rupert, Marian; Skopek, Petr; Obsil, Tomas; Zemkova, Hana (Journal of neurochemistry, 2015)
In the sustained presence of agonist, the opening of P2X7R channel is followed by pore dilatation, which causes an increase in its permeability to larger organic cations, accompanied by receptor sensitization. To explore the molecular mechanisms by which the conductivity and sensitivity are increased, we analyzed the electrophysiological properties and YO-PRO-1 uptake of selected alanine mutants in the first and second transmembrane domains of the rat P2X7R. Substitution of residues Y40, F43, G338, and D352 with alanine reduced membrane trafficking, and the D352A was practically non-functional. The Y40A and F43A mutants that were expressed in the membrane lacked pore dilation ability. Moreover, the Y40A and Y40F displayed desensitization, whereas the Y40W partially recovered receptor function. The G338A/S mutations favored the open state of the channel and displayed instantaneous permeability to larger organic cations. The G338P was non-functional. The L341A and G345A displayed normal trafficking, current amplitude, and sensitization, but both mutations resulted in a decreased pore formation and dye uptake. These results showed that the increase in P2X7R conductivity and sensitivity is critically dependent on residues Y40 and F43 in the TM1 domain and that the region located at the intersection of TM2 helices controls the rate of large pore opening. We investigated the mechanism of the proapoptotic receptor P2X7R's large pore opening and its sensitization. We found that aromatic residues in the upper part of the first transmembrane domain (TM1) are critical for both the P2X7R channel pore opening and receptor sensitization, and residues located at or below the intersection of the second transmembrane domains (TM2) control the rate of pore opening. These findings identify new residues involved in pore formation of P2X7R.
Keywords: Patch-Clamp Techniques; Protein Transport; Protein Structure, Tertiary; Amino Acid Sequence; zvířata; terciární struktura proteinů; Mutagenesis, Site-Directed; lidé; HEK293 Cells; Rats; mutageneze cílená; mutace; Molecular Sequence Data; metoda terčíkového zámku; Receptors, Purinergic P2X7; sekvence aminokyselin; molekulární sekvence - údaje; transfekce; HEK293 buňky; krysa rodu Rattus; purinergní receptory P2X7; Mutation; Humans; transport proteinů; Animals; Transfection